Amazonian mixed-species flocks demonstrate flexible preferences for vertical forest structure - Coddington, Charles P. J.; Cooper, W. Justin; Rutt, Cameron L.; Mokross, Karl [UNESP]; Amaral, Bruna R.; Stouffer, Philip C.; Luther, David A. (Wiley, 2023)
How species interact with human-disturbed environments is a central focus of conservation biology. Within disturbed landscapes, regenerating forests have potential to provide habitat for forest species, especially as increasing amounts of primary forest are lost. As secondary forest regenerates beside primary forest, it increases habitat heterogeneity. However, relatively little is known about the influence of habitat heterogeneity on space use. In this study, we analyzed the topography and vertical vegetation structure of regenerating forest, small forest fragments, and undisturbed rainforest in the central Amazon to determine (1) how these structural characteristics influence understory mixed-species flock space use and (2) how the vegetative preferences of flocks varied across a disturbance gradient. We first used behavioral observations to quantify the vertical foraging niche of flocks and then associated variation in horizontal space use with the three-dimensional features of forest structure. Surprisingly, we found that flock space use was not consistently associated with any variable, even though available habitat differed both within and across forest types. Overall, the best predictors were elevation and leaf area density within the subcanopy (16–25 m), yet most flock foraging occurred in the midstory (6–15 m). Together, these results indicate that while flocks may have certain habitat preferences, these preferences are flexible or idiosyncratic and do not correspond to a specific vertical profile. For example, flocks spent a disproportionate amount of time in low elevations when available, but not all flocks had access to low-lying areas within their home ranges. Although other studies show flock size and diversity can be highly sensitive to habitat disturbance, mixed-species flocks demonstrate remarkable plasticity as a unit, virtually saturating undisturbed and disturbed forest at our site, as long as regeneration has passed a certain threshold.
Keywords: avian; forest fragmentation; habitat quality; leaf area density; LiDAR; mixed-species flocks; secondary forests; tropical forest; vegetation structure